Barriers and facilitators to successful implementation of media education programs for older adults: Scoping review - Bobrowicz-Campos, E.; Matos, A. P. M. (2º Congresso Internacional Age.Comm Longevidade e Desenvolvimento. Livro de Resumos., 2021)
Digital transformation can bring many benefits to people's lives. However, in the absence of education programs targeting citizens with limited capacity to take advantage from its outcomes, digital transformation can contribute to the replication or even increase in existing offline inequalities. This scoping review, developed within the context of the COMEDIG project (PTDC/CED-EDG/32560/2017), aimed to map the barriers and facilitators to successful implementation of media education programs for older adults. The review process was based on the Joanna Briggs Institute procedures and considered studies that focused on identifying factors that interfere with successful implementation of media education programs for persons who are aged 60 years or over, who are retired or who benefit from institutional support specifically designed for the aged population. The programs should aim at promoting competences related to the use of media, critical analysis of media messages and/or creation of new content and its communication to others, and could be implemented in any type of community setting or geographical location. Data considered for analysis should be obtained based on feedback from recipients of the programs of interest or from their family members, media education trainers or other interested parties. Databases were searched for published and unpublished primary and secondary studies, written in English, Spanish and Portuguese, from January 2001 to September 2020. Of 1275 records identified through searching in databases, 69 full-texts were assessed for inclusion criteria and 19 were included. Based on the testimonies of older adults and/or stakeholders, five factors responsible for successful implementation of media education programs in the target population were identified. Those factors were related with organizational and pedagogical aspects of the educational programs themselves, profiles of educators involved in the teaching-learning processes and educational resources and technologies chosen to assist the pedagogical actions. They also referred to the characteristics of the persons to whom the referred programs are directed and the openness of the community to share and support the older adults in applying their media-related knowledge and skills in daily activities. It is expected that this review findings will provide an evidence-based overview of best practices in terms of media education programs targeting older adults, namely with respect to factors related to pedagogical dimensions, educational resources and educators actions, and thus, contribute to overcoming the existing barriers in relation to the participation of older adults in the digital transformation, increasing these citizens’ access to associated benefits.